Circulating Procoagulant Microparticles in Women with Unexplained Pregnancy Loss: a New Insight - Laude, I.; Rongières-Bertrand, C.; Boyer-Neumann, C.; Wolf, M.; Mairovitz, V.; Hugel, B.; Freyssinet, J. M.; Frydman, R.; Meyer, D.; Eschwège, V. (Thrombosis and Haemostasis, 2001)
One of the frequently proposed mechanisms for pregnancy losses refers to uteroplacental thrombosis. However the contribution of classical thrombotic risk factors remains questionable and, if real, does not account for a large number of pregnancy losses. The aim of this study was to investigate the presence of circulating procoagulant microparticles, a new marker of cell activation already associated with various prothrombotic clinical settings. Microparticles were assessed by an original prothrombinase assay on platelet depleted plasma obtained from 74 women with a history of pregnancy loss without apparent cause and 50 controls. Patients were studied at least 2 months after the last obstetrical event and were classified into 2 groups: 49 women with at least 3 consecutive spontaneous abortions at or before the 10th postmenstrual week and 25 with at least one fetal death beyond the 10th postmenstrual week. Among the 74 patients, 41 had increased levels of circulating microparticles, 29 belonging to the group of early pregnancy loss (59%) and 12 to the group of late pregnancy loss (48%). The high prevalence of increased levels of procoagulant microparticles in both groups makes this new marker very promising for the understanding, follow up and therapeutical handling of pregnancy loss.
Keywords: Microparticles; unexplained pregnancy loss